Effect of Chronic Valproic Acid Treatment on Hepatic Gene Expression Profile in Wfs1 Knockout Mouse. (1st April 2014) - Punapart, Marite; Eltermaa, Mall; Oflijan, Julia; Sütt, Silva; Must, Anne; Kõks, Sulev; Schalkwyk, Leonard C.; Fernandes, Catherine; Vasar, Eero; Soomets, Ursel; Terasmaa, Anton
Abstract : Valproic acid (VPA) is a widely used anticonvulsant and mood-stabilizing drug whose use is often associated with drug-induced weight gain. Treatment with VPA has been shown to upregulate Wfs1 expression in vitro . Aim of the present study was to compare the effect of chronic VPA treatment in wild type (WT) and Wfs1 knockout (KO) mice on hepatic gene expression profile. Wild type, Wfs1 heterozygous, and homozygous mice were treated with VPA for three months (300 mg/kg i.p. daily) and gene expression profiles in liver were evaluated using Affymetrix Mouse GeneChip 1.0 ST array. We identified 42 genes affected by Wfs1 genotype, 10 genes regulated by VPA treatment, and 9 genes whose regulation by VPA was dependent on genotype. Among the genes that were regulated differentially by VPA depending on genotype was peroxisome proliferator-activated receptor delta ( Ppard ), whose expression was upregulated in response to VPA treatment in WT, but not in Wfs1 KO mice. Thus, regulation of Ppard by VPA is dependent on Wfs1 genotype.